Sub-nanoscale free volume and local elastic modulus of chitosan–carbon nanotube biomimetic nanocomposite scaffold-materials. Issue 16 (28th April 2015) - Axpe, Eneko; Bugnicourt, Loic; Merida, David; Goiriena-Goikoetxea, Maite; Unzueta, Iraultza; Sanchez-Eugenia, Ruben; Garcia, Jose Angel; Plazaola, Fernando; Contera, Sonia
<x xml:space="preserve">Abstract</x> Nanoscale elastic modulus and mass transport properties calculated with free volume theory of biomimetic nanocomposite scaffolds for tissue engineering and 3D cell cultures applications.